Edukasi Kesehatan Kognitif dan Senam Otak Lansia Menuju Lansia Mandiri dan Bahagia pada Ibu-Ibu Penggerak PKK Desa Mliwis, Boyolali, Jawa Tengah - Juwita Rahmawati; Tri Yulianti; Annisa Nur Lathifah Amanda Putri; Septiana Windarti; Arini Fadhilah Fadhilah; Arifah Sri Wahyuni; Anita Sukmawati; Peni Indrayudha; Gunawan Setyadi; Febri Wulandari; Teguh Imanto; Santhyami Santhyami (Universitas Muhammadiyah Surakarta, 2025)
A prevalent issue among the elderly is cognitive deterioration. Modifications in behavior and the adoption of a healthy lifestyle have been demonstrated to mitigate cognitive decline in the elderly. The objective of community service initiatives is to disseminate knowledge regarding cognitive health in the elderly and to offer brain workouts to the community, particularly targeting women who are PKK activists in Mliwis Village. This community service initiative employs an instructional methodology that incorporates PowerPoint presentations and leaflets, utilizing a one-group pre-test and post-test design. The event took place at the Posyandu Sidorejo in Mliwis Village, Boyolali. The target audience for this activity was PKK mothers in Mliwis Village, Boyolali Regency, Central Java. To measure the level of knowledge about cognitive health, a questionnaire developed by the community service team was used. This activity consisted of six stages, namely opening, pretest, education, group brain exercises, discussion, and post-test. 51 participants, comprising PKK mothers, attended this activity. The most extensive age range was 31-40 years old, with 16 (31.4%) participants, and the largest occupation was housewife, with 36 (70.6%) participants. The education and discussion activities went well. The enthusiasm of the participants also increased with the joint brain exercises. The average pretest and posttest scores were 90.26 ± 10.78 and 93.68 ± 7.50, respectively. There was a significant difference in knowledge between the pretest and post-test measurements (p = 0.034; < 0.05). It is hoped that this educational activity will help form independent and happy elderly people.